Taming Ultrafast Laser Filaments for Optimized Semiconductor–Metal Welding - Chambonneau, Maxime; Li, Qingfeng; Fedorov, Vladimir Yu.; Blothe, Markus; Schaarschmidt, Kay; Lorenz, Martin; Tzortzakis, Stelios; Nolte, Stefan (Laser & Photonics Reviews, 2021)
Ultrafast laser welding is a fast, clean, and contactless technique for joining a broad range of materials. Nevertheless, this technique cannot be applied for bonding semiconductors and metals. By investigating the nonlinear propagation of picosecond laser pulses in silicon, it is elucidated how the evolution of filaments during propagation prevents the energy deposition at the semiconductor–metal interface. While the restrictions imposed by nonlinear propagation effects in semiconductors usually inhibit countless applications, the possibility to perform semiconductor–metal ultrafast laser welding is demonstrated. This technique relies on the determination and the precompensation of the nonlinear focal shift for relocating filaments and thus optimizing the energy deposition at the interface between the materials. The resulting welds show remarkable shear joining strengths (up to 2.2 MPa) compatible with applications in microelectronics. Material analyses shed light on the physical mechanisms involved during the interaction.
CRIS-Team Scopus Importer:2023-04-20
Keywords: copper; filamentation; material analyses; nonlinear propagation; semiconductor; silicon; ultrafast laser welding